A Country Scenarioes of Food Security and Governance in Bangladesh (Journal of Science Foundation, 2013)
The Government of Bangladesh has identified food security as an important factor contributing to its socio-economic stabilization and development. Bangladesh has made a steady progress in the expansion of food production. But because of the increasing population pressure there has been an extensive use of land to meet the growing demand for food. Despite the growth in food production and its availability, food insecurity is still a major problem mainly because of the lack of purchasing power and thus of access to food, especially for the ultra poor community. This paper focuses on the availability of food as an essential element of the concept of food security and role of government to get food sufficiency. In addition to rice and wheat that constitute the staple food of Bangladesh, the paper deals with the production and availability issues of other major food commodities, such as potato, pulses, oilseeds, vegetables and fruits, and fisheries and livestock products. The food production of the country both rice and wheat, was 10.46 million metric tons in the 1971-72. Bangladesh attained self sufficiency in food production in 2010-2011 with a gross production of rice and wheat of 35.3 million metric tons which marginally met the countrys requirement of 23.64 million metric tones for the population of 148.69 million, taking 453.6 g per capita per day requirement. Production of vegetables and fruits has increased, from 1.5 million tons and 1.46 million tons in 2001-02 to 7.19 million tons and 3.56 million tons in 2009-10 respectively. Fish production increase from 2.0 million tons in 2001-02 to 3.0 million tons in 2010-11. Livestock product (meat, milk and egg) has also increase 50% over that last ten years. Of these, domestic production is critical in ensuring food availability at both national and household levels. Government of Bangladesh is trying to integrate and address all the elements associated with food security to achieve touch the MDG setting for the country. However, in recent years, the Government is putting additional efforts to increase production of important food crops as well as fisheries and livestock. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14646 J. Sci. Foundation, 9(1&2): 41-50, June-December 2011